2022
DOI: 10.3233/bmr-210021
|View full text |Cite
|
Sign up to set email alerts
|

Infodemiology of Bell’s palsy: Tracing the seasonality of facial paralysis

Abstract: BACKGROUND: Although there are a few studies on the seasonality of facial paralysis, no studies have utilized internet data for this purpose. The use of internet data to investigate diseases and user-contributed health-related content is increasingly prevalent, and has earned the name “infodemiology”. OBJECTIVE: This study aims to use Google Trends data to investigate whether there is a seasonal variation in facial paralysis. METHODS: In this observational study, the search volume for the terms “facial paralys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In Taiwan, the fluVc is only administered for a short period each year, especially from October to December, middle autumn to early winter . It may take bias when using SCCS if the incidence of BP varies with different seasons, which is a concern because previous studies have examined the association between seasonal variation and the onset of BP . Fortunately, the present findings indicated that seasonality did not affect BP incidence in this SCCS.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In Taiwan, the fluVc is only administered for a short period each year, especially from October to December, middle autumn to early winter . It may take bias when using SCCS if the incidence of BP varies with different seasons, which is a concern because previous studies have examined the association between seasonal variation and the onset of BP . Fortunately, the present findings indicated that seasonality did not affect BP incidence in this SCCS.…”
Section: Discussionmentioning
confidence: 61%
“…6,7,9 It may take bias when using SCCS if the incidence of BP varies with different seasons, which is a concern because previous studies have examined the association between seasonal variation and the onset of BP. 22,[44][45][46][47] Fortunately, the present findings indicated that seasonality did not affect BP incidence in this SCCS. The diagnosis of BP is made after various conditions that mimic BP have been excluded.…”
Section: Discussionmentioning
confidence: 73%